Integration of artificial intelligence in medical education:: developing a framework for curriculum enhancement - Canelas-Pais, Mariana; Silva, Renato Ferreira da; Duarte, Ivone; Rodrigues, Pedro Pereira; Cruz-Correia, Ricardo (Revista Fontes Documentais, 2024)
In recent years, the field of medical education has been embracing innovative approaches to enhance the learning experience of students. One such approach is the integration of artificial intelligence (AI) technologies, including Natural Language Processing (NLP) models, Language Modeling (LLM), and chatbots. Chatbots offer a unique and interactive learning experience for medical students. These AI-driven conversational agents simulate human-like conversations, enabling students to engage in personalized interactions that serve their individual learning needs. By leveraging NLP models and LLM, chatbots can comprehend and respond to natural language queries, providing students with immediate feedback, guidance, and access to relevant resources.